Designing Virtual Field Trip Learning Media on Natural features Topic in Elementary School - Tuti Nuryani; Komariah Komariah; Yona Wahyuningsih (Universitas Tanjungpura, 2022)
This study was motivated by the lack of development of digital media in social studies learning for fifth grade the concept of natural features. The concept contains a wide and varied subject matter, so it must be packaged in an attractive media. This study aims to find knowledge related to the virtual field trip media design, determine the feasibility of the media from the validation results of material experts, linguists, and media experts, and determine the responses of teachers and students to the use of media. By using video media, Virtual Field Trips can take students to places they have never seen or visited in person. The method used in this research is Design and Development using the ADDIE model development. This research produces a product in the form of virtual field trip learning media on the natural features of social studies fifth grade elementary school. The participants of this study consisted of material expert lecturers, linguists, and media experts to provide an assessment of this learning media. Data collection techniques were carried out using questionnaires and interviews. The results of this study indicate that the virtual field trip learning media is considered very feasible as a medium that can be used in learning. This can be seen from the results of the validation by three experts, namely material experts, linguists, and media experts on each aspect of the virtual field trip media getting a score of 79.26% with a